2015
DOI: 10.1073/pnas.1515276112
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional read-through is not sufficient to induce an epigenetic switch in the silencing activity of Polycomb response elements

Abstract: In Drosophila, Polycomb (PcG) and Trithorax (TrxG) group proteins are assembled on Polycomb response elements (PREs) to maintain tissue and stage-specific patterns of gene expression. Critical to coordinating gene expression with the process of differentiation, the activity of PREs can be switched "on" and "off." When on, the PRE imposes a silenced state on the genes in the same domain that is stably inherited through multiple rounds of cell division. When the PRE is switched off, the domain is in a state perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
34
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 43 publications
3
34
0
Order By: Relevance
“…PcG protein complexes are bound at intronic PREs of HOX genes in cells where these genes are actively transcribed, both in developing Drosophila (10-12) and in tissue culture cells (13). Similar to the situation at the reporter gene in the Erokhin et al study (1), the level of PcG protein binding at such intronic PREs is somewhat reduced when analyzed by chromatin immunoprecipitation, suggesting that the act of transcription may to some extent interfere with PcG complex binding, but certainly does not result in complete removal of these protein complexes.…”
mentioning
confidence: 80%
See 4 more Smart Citations
“…PcG protein complexes are bound at intronic PREs of HOX genes in cells where these genes are actively transcribed, both in developing Drosophila (10-12) and in tissue culture cells (13). Similar to the situation at the reporter gene in the Erokhin et al study (1), the level of PcG protein binding at such intronic PREs is somewhat reduced when analyzed by chromatin immunoprecipitation, suggesting that the act of transcription may to some extent interfere with PcG complex binding, but certainly does not result in complete removal of these protein complexes.…”
mentioning
confidence: 80%
“…In 2005, Schmitt, Prestel, and Paro (9) reported that transcription through the same Fab-7 fragment (again 3.6 kb) caused switching from a repressor to an activator, but only if the transcription was continuous, at least through embryogenesis, and the authors proposed that PcG proteins would be knocked off by transcription through PREs. With their data, Erokhin et al (1) argue that this is not the case because even prolonged transcription through the PRE in their transgene does not result in displacement of PcG protein complexes. Does persistent transcription through PREs permanently displace Polycomb proteins in their native chromosomal context?…”
mentioning
confidence: 96%
See 3 more Smart Citations